THE CONSTITUTIONALIZATION OF FAMILY LAW AND THE CONSTITUTIONAL PRINCIPLES THAT SUPPORT SOCIAL-AFFECTIVITY (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
The constitutionalization of Family Law has generated numerous effects, among them, the legal recognition of social-affectivity through doctrinal and jurisprudential advances. Thus, the general objective of this paper is to analyze the constitutional principles that underlie the social-affectivity. Furthermore, it has as specific objectives: to broaden the knowledge about the constitutionalization of Family Law; to study socio-affectivity; and to research constitutional principles. Therefore, the research problem consists in answering the following question: which constitutional principles underlie and guide the social-affectivity? To do so, the deductive method was used, as well as bibliographical and documental methodology regarding the procedure, descriptive in relation to the objectives, and qualitative regarding the approach. Finally, it was understood that the constitutional principles that support the legal recognition of social-affectivity are: human dignity; freedom; equality of filiation and respect for difference; pluralism of family entities; best interests of children and adolescents; prohibition of social regression; pursuit of happiness and affection.